واقع تطبيق scfفي مؤسسة الضمان الاجتماعي - كيرد, شوقي; كرمادي, الحاج الطيب; مصطفاوي, بدر الدين (University of eloued جامعة الوادي, 2017)
The objective of this study is to study the financial accounting system in the social security institution,abd that by clarifying the accounting insurance operations, which has a great role in Economic life. The importance of the topics dealing with social security accounting, which is undergoing a transition to the financial accounting system, has become problematic. This study tackled the problem of how the financial accounting system in the social security institution. After our applied study, the study concluded that the application of the financial accounting system has an advantage in the study of the insurance operations ,and also this system facilitates accounting operations and coordinates services between the departments in the social security institution.
مذكرة ماستر تدقيق محاسبي
Keywords: نظام محاسبي مالي، عمليات التامين، ضمان اجتماعي; Financial Accounting System, Insurance operations, social